2020
DOI: 10.1155/2020/5217215
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Resistance and Reliability Analysis of Recycled Aggregate Concrete in a Sulfate Environment

Abstract: Resistance to sulfate degradation is an important index used to measure concrete's durability. In this study, recycled aggregate concrete (RAC) with a 0%, 30%, and 50% recycled coarse aggregate substitution rate and a 0% and 15% recycled fine aggregate replacement rate was used as the research object, and its degradation resistance was evaluated by the mass loss rate and the relative dynamic modulus of elasticity. e degradation products were studied and analyzed with SEM scanning electron microscopy and XRD ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…With more drying and wetting cycles, more SO 4 2− invades TWGPC, leading to a rapid chemical reaction. The resulting product absorbs water and generates a swelling force, which destroys the internal structure of TWGPC, leading to an increase in the relative value of the decline rate of the dynamic elastic modulus (Cao et al 2020).…”
Section: Relative Dynamic Modulus Of Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…With more drying and wetting cycles, more SO 4 2− invades TWGPC, leading to a rapid chemical reaction. The resulting product absorbs water and generates a swelling force, which destroys the internal structure of TWGPC, leading to an increase in the relative value of the decline rate of the dynamic elastic modulus (Cao et al 2020).…”
Section: Relative Dynamic Modulus Of Elasticitymentioning
confidence: 99%
“…To effectively solve the problems of a low utilization rate of solid waste and large environmental pollution (Zhao et al 2020), FA can be used to partially replace cement, tailings and waste rock can be used to replace natural sand, and breakstone can be utilized to prepare concrete (Dandautiya and Singh 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In some of previous studies, no signi cant negativity was observed in sulfate resistance of concrete when using RA. They explained this result with RFAs absorbing more sulfate solution because of their more porous structure(Cao et al 2020). Similar results were observed also in the study carried out by Bing et al(Qi et al 2017).…”
mentioning
confidence: 98%